Tráfico ilegal de hidrocarburos en la frontera sur de Ecuador. - Añazco Campuzano, Darío Javier (2015)
The illegal trafficking of fuel is not a new phenomenon, this was born as the subsidy for petroleum products, is public knowledge that on the southern border of our country this kind of illegal activities such as smuggling are made, since networks crime growing international mobility and their ability to seize opportunities arising from the separation of markets in sovereign states with borders, especially the smuggling of gasoline, diesel and liquefied gas.